Tereré: uma leitura de muitas vozes - Pedrosa, Nilma Alves (2021)
This thesis aims to present an intervention that is based on a way of reading focused on the possibility of mobilization and on the somatic involvement of the reader in the world of things - learners between 5-12 years old, from Praia do Forte district, north coast of the State from Bahia - as well as investigating how this process is exposed to contribute to the reading proficiency of these readers. It is based on a hybrid dimension of consciousness - subject to the temporal flow, but open to spatial possibilities - that triggers in the reader the living experience of reading, which is not reduced to the production of meaning, but is converted into reflection. It is speculated, therefore, that the living experience resists interpretation and provides a fleeting cosmological place to the reader - which is understood by many voices - and allows the affective experience of multiple possibilities through the interaction between practices and representations. For this clarification, the idea of the aspects of reading representation from Classical Antiquity to Modernity is developed, looking for evidence of the various coercions (social, historical, ideological) to ground in the subsequent discussion of the theme. It takes place in the dialogue of representations according to Schopenhauer and Spinoza (matrixes), in the studies on reading by Chartier and Dehaene on the act of reading (mentalities) and in the understanding of practical activities such as “world readings”, by educator Paulo Freire (processes). Philosophical debate that applies to reading, encompassed both cultural theory (Vygotsky) and cultural history, as well as discourse analysis (Foucault) for a reflection on the representations that subjects share of what it means to be a reader. The methodology used, action research, has agreed with subjects and researcher interconnecting the theme - representations of reading practices - the essence of how an intervention can encompass new elements. Constituents that, collectively, provided a character of word-gesture, word-idea and plastic-word to reading, interpenetrating the external reality of the community and the affections of readers. Experiences lived that circumscribed the representation-affect mode of reading and choreographed a bioconstruction of collective participation. Practices in accordance with the ecological concern, present from conception to occupation, which in an efficient, effective and satisfactory way, enabled learners, for example, reading proficiency and competence in the experiment of bioconstructing a space made from pet bottles